2018
DOI: 10.2320/matertrans.md201702
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Microsized Magnetic Materials by Ink-Jet Printing

Abstract: Micro-magnetic structures including Nd-Fe-B microsized particles were produced by the ink-jet printing technique. The Nd-Fe-B particles were commercial MQP-B particles with a Nd 2 Fe 14 B phase and an average diameter of 6 µm. The particles were milled to a mean particle size of about 300 nm before being added to the standard ink, MFL-003. The resultant magnetic suspension contained nanosized Nd-Fe-B particles with a suitable weight percentage (43%) and displayed a negligible difference in parameters, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Furthermore, the magnetic structures supply the magnetic field source without energy dissipation and heating. For these reasons, several techniques have been developed to fabricate magnetic structures such as the electroplating method, 10) the self-assembly method, 11) the topographically patterned method, 12) the ink-jet printing, 13) and the magnetic imprinting. 14) The last one is a simple and low-cost method to fabricate rapidly the arrays of magnetic clusters without using high-tech fabrication systems and vacuum techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the magnetic structures supply the magnetic field source without energy dissipation and heating. For these reasons, several techniques have been developed to fabricate magnetic structures such as the electroplating method, 10) the self-assembly method, 11) the topographically patterned method, 12) the ink-jet printing, 13) and the magnetic imprinting. 14) The last one is a simple and low-cost method to fabricate rapidly the arrays of magnetic clusters without using high-tech fabrication systems and vacuum techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction of carboxylic acid headgroups of arachidic acid (AA) monolayers with trivalent ions Fe 3+ and La 3+ was studied using vibrational sum-frequency generation (VSFG) spectroscopy by Nguyen et al 189) In the fifth category of the advanced processing of nanomaterials, six attractive studies were summarized. First work is for the fabrication of micron-sized magnetic materials by ink-jet printing by Cuong et al 190) They synthesized squared magnetic patterns on the substrate as shown in the inset(1) in Fig. 5 and observed the magnetic property of such patterns.…”
mentioning
confidence: 99%